Back Cover: Autofluorescence and white light imaging‐guided endoscopic Raman and diffuse reflectance spectroscopy for in vivo nasopharyngeal cancer detection (J. Biophotonics 4/2018). Issue 4 (17th April 2018) - Lin, Duo; Qiu, Sufang; Huang, Wei; Pan, Jianji; Xu, Zhihong; Chen, Rong; Feng, Shangyuan; Chen, Guannan; Li, Yongzeng; Short, Michael; Zhao, Jianhua; Fawzy, Yasser; et al.
Abstract : An integrated 4‐modality endoscopy system combining white light imaging, autofluorescence imaging, diffuse reflectance spectroscopy and Raman spectroscopy technologies was developed for in vivo endoscopic nasopharyngeal cancer detection. Both high diagnostic sensitivity (98.6%) and high specificity (95.1%) for differentiating cancer from normal tissue sites were achieved using this system combined with multivariate diagnostic algorithm, demonstrating great potential for improving real‐time, in vivo diagnosis of cancer at endoscopy. Further details can be found in the article by Duo Lin et al. (e201700251 ) Abstract : An integrated 4‐modality endoscopy system combining white light imaging, autofluorescence imaging, diffuse reflectance spectroscopy and Raman spectroscopy technologies was developed for in vivo endoscopic nasopharyngeal cancer detection. Both high diagnostic sensitivity (98.6%) and high specificity (95.1%) for differentiating cancer from normal tissue sites were achieved using this system combined with multivariate diagnostic algorithm, demonstrating great potential for improving real‐time, in vivo diagnosis of cancer at endoscopy. Further details can be found in the article by Duo Lin et al. (e201700251 )